Stress reaction and Post-traumatic stress disorder among flood victims of Lahore- Pakistan and role of community (ROC) - Dr , Amina Nasar (International Journal of Psychosocial Rehabilitation, 2016)
Aims and Objectives: The present study investigated the relationship between stress reaction, Post-Traumatic Stress Disorder (PTSD) and Role of community (ROC) among flood victims.Sample: The stratified random sampling was used to collect total sample of 130; consisted of 100 flood victims with the age range of 18 to 40 years (M=1.52, SD=3.9) and 30 community relief group workers with the age range 30-49 from most flood affected areas of district Lahore.Material and Method: Kessler stress reaction Scale and The Impact Event Scale-Revised were used to measure the stress reaction and Post-Traumatic Stress Disorder (PTSD) among flood victims after translating into Urdu language.Results and Conclusion: The study found that there was a significant positive relationship between stress reaction and Post-Traumatic Stress Disorder. Moreover Post Traumatic Stress Disorder and Education emerged as significant predictors of stress reaction.